Photoremoval of Protecting Groups: Mechanistic Aspects of 1,3- Dithiane Conversion to a Carbonyl Group - Oksdath Mansilla, Gabriela (2015)
Photodeprotection of 1,3-dithianes in the presence of thiapyrylium was performed to return to the parent carbonyl compound, and the mechanism was studied by steady state photolysis, laser flash photolysis, and theoretical calculations. Electron transfer from dithianes to triplet sensitizers is extremely fast, and the decay of dithiane radical cations was not affected by the presence of water or oxygen as the consequence of a favorable unimolecular fragmentation pathway. Similar behaviors were observed for dithianes bearing electron-releasing or electron-withdrawing substituents on the aryl moiety, evidenced by C−S bond cleavage to form a distonic radical cation species. The lack of reaction under nitrogen atmosphere, requirement of oxygen for good conversion yields, inhibition of the photodeprotection process by the presence of pbenzoquinone, and absence of a labeled carbonyl final product when the reaction is performed in the presence of H2 18O all suggest that the superoxide anion drives the deprotection reaction. Density functional theory computational studies on the reactions with water, molecular oxygen, and the superoxide radical anion support the experimental findings.